GAMBARAN PENYESUAIAN DIRI SISWA KELAS X IPA 3 SMA NEGERI 25 GARUT - Wiwin Nur Endang; Heris Hendriana; Devy Sekar Ayu Ningrum (IKIP Siliwangi, 2021)
This research aim to show how overview adjusments of student at grade X IPA 3 SMAN 25 Garut. This research used descriptive qualitative method with case study approach. The sample research is 8 students from X IPA 3 SMAN 25 GARUT. The techniques data colection are interview, direct observation and documentation study. While, the data collections used by interview guidelines, observation and documentation study. The result of this research is how to show the adjusment of student grade X IPA 3 SMAN 25 Garut stated is good. This can be seen from the aspect of maintenance from the stage adapting to the theme, teachers and the school environment are quite good.Keywords: : Adjusment, student